Inhibition of oxidative stress of Biancaea sappan (L) Tod. from Java - Tiono, Yovita Viona; Prasetyo, Agustinus Hadi; Wulanjati, Martha P.; Wink, Michael; Nurcahyanti, Agustina Dwi Retno (Natural product research, 2025)
Increased reactive oxygen species and advanced glycation end products are often associated with human ageing and degenerative diseases. Biancaea sappan L serves as a medicinal plant and a healthy drinks ingredient in Java. However, the pharmacological investigation of the plant native to this island is still lacking in depth. In the current study, DNA barcoding using the marker gene maturase K (matK), evaluation of the chemical composition, total phenolic content (TPC) and antioxidant properties, antiglycation, anti-β-amyloid, anti-inflammatory, and selective cytotoxic activities were performed. B. sappan shares well-known phytoconstituents with other members of the genus Biancaea. The heartwood ethanol extract possesses the most prominent antioxidant, anti-inflammatory, and anti-β-amyloid effects. The aqueous extract demonstrated a most substantial anti-glycation activity and was rich in phenolics. The ethanol extract from heartwood exhibited the highest cytotoxicity against SW-48, indicating B. sappan heartwood from Java holds promise as antioxidants and may selectively inhibit colorectal cancer.